Two-component polyurethane adhesive composition

By developing a thermal conductivity two-component polyurethane glue containing aluminum trihydroxide, expandable graphite and high-definition graphite, the problem that the thermal conductivity glue in the prior art cannot meet the multiple performance requirements of the automotive industry during application, and the effects of high thermal conductivity, strong adhesive force and appropriate extension are achieved.

JP2025512998APending Publication Date: 2025-04-22DDP SPECIALTY ELECTRONICS MATERIALS US LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024559458
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-08-05
Filing Date
2023-04-05
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

During the application process, the thermally conductive contact materials and thermally conductive adhesives in the prior art cannot meet the needs of the automotive industry in terms of application process, curing speed, strength, impact performance requirements, durability and exposure performance.

Method used

A thermally conductive two-component polyurethane glue is developed, which consists of at least one polyamine and a polyethanol polyester alcohol. The first component comprises aluminum trihydroxide having a multimodal particle size distribution, expandable graphite and pattern or graphite having a longitudinal ratio greater than 2. The second component also contains these thermally conductive fillers to ensure that the thermally conductive filler concentration after mixing reaches 40-80% by weight percent.

Benefits of technology

It achieves high thermal conductivity, strong adhesive force and appropriate extension, and meets the multiple performance requirements of the automotive industry for thermal conductivity adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512998000001
    Figure 2025512998000001
  • Figure 2025512998000002
    Figure 2025512998000002
  • Figure 2025512998000003
    Figure 2025512998000003
Patent Text Reader

Abstract

Provided herein are two-part polyurethane adhesive compositions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 63 / 327,862, filed April 6, 2022, and U.S. Provisional Patent Application No. 63 / 395,433, filed August 5, 2022, both of which are incorporated by reference into this application.

[0002] The present invention relates to the field of two-part polyurethane adhesive compositions. [Background technology]

[0003] Modern vehicle design is seeing an increase in the use of adhesive technologies and adhesive bonding. Adhesive bonding is the most preferred assembly technique because the bond maintains the integrity of the assembled parts (as opposed to mechanical fastenings such as screwing or riveting). In addition, the continuous bond line made possible by adhesives improves the performance of the joined parts and modules. The continuous bond line imparts torsional stiffness and high crashworthiness to the parts, modules, and the entire vehicle body.

[0004] A fast adhesive application process and a heat accelerated curing process reduce tack times and speed up the assembly process. These same advantages of adhesive bonding also apply to the assembly of battery modules in electric vehicles. Adhesive bonding imposes stringent crash and crunch performance requirements on the battery compartment. In addition to structural requirements, the design of the battery module and battery compartment must meet thermal management requirements. Heat generated during battery operation must be transferred to the cooling unit. This requires heat transfer between battery cells, between battery modules, or between the battery compartment and the cooling unit.

[0005] There are thermally conductive interface materials available on the market. There are also thermally conductive adhesives available for the electronics industry. Thermal conductivity is mainly achieved using thermally conductive fillers. However, the application process, curing speed, strength, crash performance requirements, durability, and exposure resistance of these materials do not meet the requirements of the automotive industry. Summary of the Invention [Means for solving the problem]

[0006] In a first aspect, the present invention provides a thermally conductive two-part polyurethane adhesive comprising: (A) (a1) at least one polyisocyanate a first component (isocyanate component) comprising: (B) (b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; and a second component (polyol component) comprising: and wherein component A and / or component B are (i) aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; (iii) graphene and / or graphite having an aspect ratio greater than 2; (a2, b3) containing a thermally conductive filler; the concentration of the thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 weight percent in the adhesive when Components A and B are mixed together to form the adhesive; Provide an adhesive.

[0007] In a second aspect, the present invention provides a thermally conductive two-part polyurethane adhesive prepared by mixing a first component (A) and a second component (B), (A)(a1) at least one polyisocyanate, and (B) (b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; Includes; Component A and / or component B (i) aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; (iii) graphene and / or graphite having an aspect ratio greater than 2; (a2, b3) containing a thermally conductive filler; the concentration of the thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 weight percent in the adhesive when Components A and B are mixed together to form the adhesive; Provide an adhesive.

[0008] In a third aspect, the present invention provides a method of bonding two or more substrates, comprising the steps of: (1) providing a thermally conductive two-part polyurethane adhesive, the thermally conductive two-part polyurethane adhesive comprising: (A) (a1) at least one polyisocyanate a first component (isocyanate component) comprising: (B) (b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; and a second component (polyol component) comprising: and wherein component A and / or component B are (i) aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; (iii) graphene and / or graphite having an aspect ratio greater than 2; (a2, b3) containing a thermally conductive filler; the concentration of the thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 weight percent in the adhesive when Components A and B are mixed together to form the adhesive; (2) mixing component A with component B to produce an adhesive; (3) applying an adhesive to a first substrate; (4) bringing a second substrate into adhesive contact with the first substrate; and (5) Curing the adhesive The present invention provides a method comprising:

[0009] In a fourth aspect, the present invention provides a method for producing a pharmaceutical composition comprising the steps of: (1) a first substrate; (2) a second substrate adhesively bonded to the first substrate by a cured adhesive; and A bonded structure comprising: The cured adhesive is obtained by curing a mixture of a first component (A) and a second component (B), which components are (A)(a1) at least one polyisocyanate, and (B) (b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; Includes; Component A and / or component B (i) aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; (iii) graphene and / or graphite having an aspect ratio greater than 2; (a2, b3) containing a thermally conductive filler; the concentration of the thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 weight percent in the adhesive when Components A and B are mixed together to form the adhesive; Provide a bonded structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The inventors have discovered that excellent thermal conductivity, high bond strength, and adequate elongation can be achieved using the two-part polyurethane adhesive of the present invention.

[0011] Definitions and Abbreviations MDI 4,4'-methylenebis(phenylisocyanate) HDI Hexamethylene Diisocyanate IPDI Isophorone Diisocyanate PU Polyurethane SEC Size Exclusion Chromatography RH Relative Humidity

[0012] The equivalent weight and molecular weight were determined by gel permeation chromatography (GPC) using a Malvern Viscothek GPC max instrument. Tetrahydrofuran (THF) was used as the eluent, PL GEL MIXED D (Agilent, 300*7.5mm, 5μm) was used as the column, and MALVERN Viscotek TDA (integrated refractive index viscometer and light scattering) was used as the detector.

[0013] Ingredient A Component A is (a1) at least one polyisocyanate Includes.

[0014] At least one polyisocyanate (a1) The polyisocyanate is not particularly limited.

[0015] Aliphatic and aromatic diisocyanates can be used, with aromatic being preferred. Examples of suitable diisocyanates include toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene bis-cyclohexyl isocyanate (HMDI) (hydrogenated MDI), MDI (especially 4,4'- and 4,2-MDI), and isophorone diisocyanate (IPDI), with MDI being particularly preferred.

[0016] In a preferred embodiment, the polyisocyanates have an average NCO functionality of greater than 2, more preferably greater than or equal to 2.1, particularly preferably greater than or equal to 2.15.

[0017] The target NCO functionality can be achieved by using either a single polyisocyanate having an average NCO functionality in the target range, or a mixture of isocyanates having different average NCO functionalities in proportions to obtain the target average NCO functionality in the range.

[0018] The functionality f of the polyisocyanate is calculated as follows: f=M n / equivalent (In the formula, M n is the number average molecular weight, and "equivalent weight" is the mass in grams of the molecule divided by the number of reactive groups per molecule (for isocyanates, this is the NCO group). Alternatively, for a mixture, f = number of equivalents of mixture * number of NCOs / 42 It is.

[0019] In a preferred embodiment, the polyisocyanates have an average NCO functionality in the range of 2.1 to 4.0, more preferably 2.1 to 3.5, particularly preferably 2.15 to 3.0.

[0020] In a preferred embodiment, the polyisocyanate is selected from polymeric MDI, polycarbodiimide modified MDI, and mixtures thereof.

[0021] In a particularly preferred embodiment, the polyisocyanate is selected from polymeric MDI, polycarbodiimide modified MDI, both of which preferably have an average NCO functionality of 2.1 or greater, and mixtures thereof.

[0022] In a preferred embodiment, the polyisocyanate is a prepolymer formed by the reaction of at least one molecule having two or more isocyanate groups with a polyol, resulting in a prepolymer terminated with isocyanate groups.

[0023] In another preferred embodiment, the polyisocyanate is a prepolymer formed by the reaction of at least one molecule having two or more isocyanate groups with a polyether polyol, resulting in a prepolymer terminated with isocyanate groups.

[0024] In another preferred embodiment, the polyisocyanate is a prepolymer formed by the reaction of at least one molecule having two or more isocyanate groups and having an average NCO functionality of more than 2, more preferably 2.1 or more, particularly preferably 2.15 or more, with a polyether polyol, resulting in a prepolymer terminated with isocyanate groups.

[0025] In another preferred embodiment, the polyisocyanate is a prepolymer formed by the reaction of at least one molecule having two or more isocyanate groups with a polyether polyol diol, resulting in a prepolymer terminated with isocyanate groups.

[0026] In another preferred embodiment, the polyisocyanate is formed by the reaction of at least one molecule having two or more isocyanate groups with a polyol based on poly(propylene oxide), resulting in a prepolymer terminated with isocyanate groups.

[0027] In another preferred embodiment, the polyisocyanate is formed by the reaction of at least one molecule having two or more isocyanate groups with a poly(propylene oxide)-based diol, resulting in a prepolymer terminated with isocyanate groups.

[0028] In another preferred embodiment, the polyisocyanate is a prepolymer formed by the reaction of MDI with a polyether polyol. More preferably, the prepolymer is formed by the reaction of MDI with a polyether polyol diol.

[0029] In another preferred embodiment, the polyisocyanate is a prepolymer formed by the reaction of MDI with a polyol based on poly(propylene oxide).

[0030] In another preferred embodiment, the polyisocyanate is a prepolymer formed by the reaction of MDI with a poly(propylene oxide)-based diol.

[0031] In another preferred embodiment, the polyisocyanate is a prepolymer formed by the reaction of MDI with a first poly(propylene oxide)-based diol having an equivalent weight of 700 g / eq or greater and a second poly(propylene oxide)-based diol having an equivalent weight of 500 g / eq or less.

[0032] In another preferred embodiment, the polyisocyanate is a prepolymer formed by reacting MDI with a mixture of a first poly(propylene oxide) based diol having an equivalent weight of 1001 g / eq and a second poly(propylene oxide) based diol having an equivalent weight of 215 g / eq.

[0033] In another preferred embodiment, the prepolymer has an average NCO functionality of greater than 2.0, more preferably 2.1 or greater, and especially preferably 2.15 or greater.

[0034] In another preferred embodiment, the prepolymer is prepared by reacting MDI and / or polymeric MDI with a diol based on poly(propylene oxide), resulting in a prepolymer having an average NCO content of greater than 2.0, more preferably 2.1 or greater, and especially preferably 2.15 or greater.

[0035] The prepolymer may be formed in situ when Component A is formulated by simply mixing the polyisocyanate with the polyol when Component A is formulated.

[0036] In a particularly preferred embodiment, the polyisocyanate is a prepolymer formed by reaction of a polyisocyanate with a polyol; The prepolymer contains 65 to 85% by weight of polyisocyanate and 15 to 35% by weight of polyol. More preferably, the prepolymer contains 70 to 80% by weight of polyisocyanate and 20 to 30% by weight of polyol, based on the total weight of the prepolymer.

[0037] In a particularly preferred embodiment, the polyisocyanate is a prepolymer formed by the reaction of 65 to 85 weight percent MDI and 15 to 35 weight percent poly(propylene oxide)-based diol.

[0038] In a preferred embodiment, the prepolymer has a urethane group ("hard segment") content of greater than 20% by weight, more preferably greater than 29% by weight, and most preferably greater than 35% by weight, based on the total weight of the prepolymer. The hard segment content is calculated by adding up the weights of the aromatic and polymeric MDI used to make the prepolymer and calculating the weight percentage based on the total weight of the isocyanate component.

[0039] In preferred embodiments, the prepolymer has sufficient hard segment content so that the fully cured adhesive has a hard segment content of greater than 10 weight percent, more preferably greater than 20 weight percent, and most preferably greater than 25 weight percent.

[0040] Thermally conductive filler Component A and / or Component B include a particular thermally conductive filler package. The thermally conductive filler may be present in Component A or Component B or both, and the concentration of the thermally conductive filler in Component A and / or Component B is sufficient such that when Components A and B are mixed together to form the adhesive, the concentration of the thermally conductive filler in the adhesive is 40-80% by weight, more preferably 40-60% by weight, based on the total weight of the adhesive.

[0041] In a preferred embodiment, the thermally conductive filler is present in Component A at 40 to 80 wt %, preferably 40 to 60 wt %, based on the total weight of Component A.

[0042] In another preferred embodiment, the thermally conductive filler is present in Component B at 40 to 80 wt %, more preferably 40 to 60 wt %, based on the total weight of Component B.

[0043] In another preferred embodiment, the thermally conductive filler is present in component A at 40 to 80% by weight, more preferably 40 to 60% by weight, based on the total weight of component A, and the thermally conductive filler is present in component B at 40 to 80% by weight, more preferably 40 to 60% by weight, based on the total weight of component B.

[0044] The thermally conductive filler is preferably present in the final adhesive at a concentration that provides a thermal conductivity of about 1.1 W / mK or greater after curing for 7 days at 23°C.

[0045] When components A and B are mixed in a volume ratio of 1:1, the preferred concentration of the thermally conductive filler in component A is 40 to 80% by weight, more preferably 50 to 60% by weight, based on the total weight of component A.

[0046] When components A and B are mixed in a volume ratio of 1:1, the preferred concentration of the thermally conductive filler in component B is 40 to 80% by weight, more preferably 50 to 60% by weight, based on the total weight of component B.

[0047] The thermally conductive filler is (i) Aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; and (iii) Graphene and / or graphite with an aspect ratio greater than 2 Includes.

[0048] The term multimodal particle size distribution means that at least two major peaks are observed when particle size is plotted on the x-axis against volume percent on the y-axis.

[0049] In a preferred embodiment, the aluminum trihydroxide is bimodal.

[0050] The particle size distribution of aluminum trihydroxide is typically measured using laser diffraction techniques using water containing sodium pyrophosphate as a suspending agent.

[0051] In a preferred embodiment, the aluminum trihydroxide has the following particle size distribution: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm.

[0052] In a more preferred embodiment, the aluminum trihydroxide has the following particle size distribution: 1-10% by volume: <1μm, 5-20% by volume: 1-10μm, 6-20% by volume: 10-20μm, 5-40% by volume: 20-50μm, 35-60% by volume: 50-100μm.

[0053] In a particularly preferred embodiment, the aluminum trihydroxide has the following particle size distribution: 1-5% by volume: <1 μm, 5-15% by volume: 1-10 μm, 6-15% by volume: 10-20 μm, 20-40% by volume: 20-50 μm, 40-70% by volume: 50-100 μm.

[0054] The aluminum trihydroxide preferably comprises a mixture of aluminum trihydroxide having the following particle size distribution: ATH1. A first aluminum trihydroxide having the following particle size distribution: D 10 :10μm D 50 : 8μm D 90 :100μm; ATH2. A second aluminum trihydroxide having the following particle size distribution: D 50 : 8μm D 90 : 18μm.

[0055] In a preferred embodiment, the aluminum trihydroxide contains 75 to 90% by weight, more preferably 80 to 90% by weight, and particularly preferably 85 to 88% by weight, of ATH1, and 10 to 25% by weight, more preferably 10 to 20% by weight, and particularly preferably 12 to 15% by weight of ATH2, based on the total weight of the aluminum trihydroxide.

[0056] The total amount of aluminum trihydroxide in Component A and / or Component B is preferably 40 to 60% by weight, more preferably 45 to 55% by weight, and particularly preferably 47 to 52% by weight, based on the total weight of the corresponding components.

[0057] The thermally conductive filler includes expandable graphite. Expandable graphite is graphite that expands to several times its starting volume when heated to a temperature, typically in the range of 200°C to 250°C. The minimum expansion rate is preferably less than 100 cm 3 / g.

[0058] The expandable graphite preferably has the following particle size distribution: 1-10% by volume larger than 50 μm, 20-50% by volume larger than 150 μm, 30-80% by volume larger than 300 μm.

[0059] The particle size distribution of the expandable graphite is determined according to DIN 66165 part 1 using sieves of 63-5000 μm (according to DIN 4188).

[0060] In a preferred embodiment, the expandable graphite is a mixture of the following expandable graphites: GR1. 75% by volume of the material has a particle size of <150μm and has an expansion coefficient of 100cm 3 / g of the first expandable graphite GR2. 80% by volume of the material has a particle size of >300μm and an expansion coefficient of 250cm 3 / g of a second expandable graphite.

[0061] In a preferred embodiment, the expandable graphite contains 40 to 80% by weight, more preferably 45 to 75% by weight, and particularly preferably 50 to 75% by weight of GR1 and 40 to 80% by weight, more preferably 45 to 75% by weight, and particularly preferably 50 to 75% by weight of GR2, based on the total weight of the expandable graphite.

[0062] The total amount of expandable graphite in component A and / or component B is preferably 2 to 10% by weight, more preferably 4 to 8% by weight, and particularly preferably 6% by weight, based on the total weight of the corresponding components.

[0063] The thermally conductive fillers include graphene and / or graphite having an aspect ratio of greater than two.

[0064] Graphene is an allotrope of carbon consisting of a single layer of atoms arranged in a two-dimensional honeycomb lattice nanostructure.

[0065] In a preferred embodiment, the graphene has a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm.

[0066] The average platelet size of graphene is typically measured according to DIN 66165 part 1 using 63-5000 μm sieves (according to DIN 4188).

[0067] In another preferred embodiment, the graphite having an aspect ratio greater than 2 has an aspect ratio greater than 3, more preferably greater than 4. The graphite having an aspect ratio greater than 2 is preferably selected from graphite particles, graphene platelets, and mixtures thereof.

[0068] In a preferred embodiment, the graphite having an aspect ratio of more than 2 has a D of 80 to 110 μm, more preferably 85 to 95 μm. 90 The graphite particles have the following structure:

[0069] In another preferred embodiment, the graphite having an aspect ratio of more than 2 is a graphene nanoplatelet having a thickness of 10 to 30 nm, more preferably 16 to 20 nm, and an average particle size of 10 to 35 μm, more preferably 15 to 30 μm, particularly preferably 24 to 26 μm.

[0070] In another preferred embodiment, the graphite having an aspect ratio of more than 2 has an aspect ratio of more than 3, more preferably more than 4, and a D of 80 to 110 μm, more preferably 85 to 95 μm. 90 The compound is in the form of particles having the formula:

[0071] The amount of graphene and / or graphite having an aspect ratio greater than 2 in component A and / or component B is preferably 0.5 to 2 wt. %, more preferably 0.75 to 1.5 wt. %, particularly preferably 1 to 1.3 wt. %, based on the total weight of the respective components.

[0072] In a preferred embodiment, the thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0073] In another preferred embodiment, the thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0074] In another preferred embodiment, the thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0075] In another preferred embodiment, the thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0076] In another preferred embodiment, the thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7 to 12% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0077] In another preferred embodiment, the thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9 to 11% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0078] In a preferred embodiment, the thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 5-15% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0079] In another preferred embodiment, the thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 7-12% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0080] In another preferred embodiment, the thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 9-11% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0081] In a preferred embodiment, the thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0082] In another preferred embodiment, the thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0083] In another preferred embodiment, the thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0084] In a preferred embodiment, the thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0085] In another preferred embodiment, the thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0086] In another preferred embodiment, the thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0087] In a preferred embodiment, the thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.5-4% by weight of graphite in the form of particles having wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0088] In another preferred embodiment, the thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7-12% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1-3% by weight of graphite in the form of particles having wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0089] In another preferred embodiment, the thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9-11% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1.5-2.5% by weight of graphite in the form of particles having wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0090] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; include.

[0091] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 weight percent graphene and / or graphite having an aspect ratio greater than 2; include.

[0092] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 wt. % of graphene and / or graphite having an aspect ratio greater than 2; include.

[0093] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3 to 10 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.5 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; include.

[0094] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4 to 7 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.75 to 1.5 weight percent graphene and / or graphite having an aspect ratio greater than 2; include.

[0095] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1 to 1.3 wt. % of graphene and / or graphite having an aspect ratio greater than 2; include.

[0096] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; include.

[0097] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; include.

[0098] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; include.

[0099] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; include.

[0100] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; include.

[0101] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; include.

[0102] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3-10% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.5-3% by weight of graphite in the form of particles having include.

[0103] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4-7% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.75-1.5% by weight of graphite in the form of particles having include.

[0104] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1-1.3% by weight of graphite in the form of particles having include.

[0105] In a preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0106] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0107] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0108] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0109] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7 to 12% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0110] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9 to 11% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0111] In a preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 5-15% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0112] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 7-12% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0113] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 9-11% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0114] In a preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0115] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0116] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0117] In a preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0118] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0119] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0120] In a preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.5-4% by weight of graphite in the form of particles having wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0121] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7-12% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1-3% by weight of graphite in the form of particles having wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0122] In another preferred embodiment, the thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9-11% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1.5-2.5% by weight of graphite in the form of particles having wherein the weight percentages are based on the total weight of the thermally conductive filler.

[0123] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; include.

[0124] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 weight percent graphene and / or graphite having an aspect ratio greater than 2; include.

[0125] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 wt. % of graphene and / or graphite having an aspect ratio greater than 2; include.

[0126] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3 to 10 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.5 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; include.

[0127] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4 to 7 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.75 to 1.5 weight percent graphene and / or graphite having an aspect ratio greater than 2; include.

[0128] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1 to 1.3 wt. % of graphene and / or graphite having an aspect ratio greater than 2; include.

[0129] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; include.

[0130] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; include.

[0131] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; include.

[0132] In another preferred embodiment, the thermally conductive filler is (i) ATH1. A first aluminum trihydroxide having the following particle size distribution: D 10 :10μm D 50 : 8μm D 90 :100μm; ATH2. A second aluminum trihydroxide having the following particle size distribution: D 50 : 8μm D 90 :18μm; a mixture of aluminum trihydroxide having a particle size distribution of; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; Expandable graphite, which is an expandable graphite mixture of (iii) graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Includes.

[0133] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; include.

[0134] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; include.

[0135] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; include.

[0136] In another preferred embodiment, the thermally conductive filler is (i) ATH1. A first aluminum trihydroxide having the following particle size distribution: D 10 :10μm D 50 : 8μm D 90 :100μm; ATH2. A second aluminum trihydroxide having the following particle size distribution: D 50 : 8μm D 90 :18μm; a mixture of aluminum trihydroxide having a particle size distribution of; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; Expandable graphite, which is an expandable graphite mixture of (iii) graphite having an aspect ratio greater than 3, more preferably greater than 4; Includes.

[0137] In a preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3-10% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.5-3% by weight of graphite in the form of particles having include.

[0138] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4-7% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.75-1.5% by weight of graphite in the form of particles having include.

[0139] In another preferred embodiment, the adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1-1.3% by weight of graphite in the form of particles having include.

[0140] In another preferred embodiment, the thermally conductive filler is (i) ATH1. A first aluminum trihydroxide having the following particle size distribution: D 10 :10μm D 50 : 8μm D 90 :100μm; ATH2. A second aluminum trihydroxide having the following particle size distribution: D 50 : 8μm D 90 :18μm; a mixture of aluminum trihydroxide having a particle size distribution of; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; Expandable graphite, which is an expandable graphite mixture of (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 Graphite in the form of particles having; Includes.

[0141] Polyether polyol (b1) Component B comprises at least one polyether polyol. The at least one polyether polyol is preferably a diol, a triol or a tetraol. Preferably, it is a diol, a triol or a mixture of triols and diols, with mixtures of diols and triols being particularly preferred.

[0142] Polyether polyols are well known in the art and include, for example, polyoxyethylene, polyoxypropylene, polyoxybutylene, and polytetramethylene ether diols and triols, which can be prepared, for example, by reacting ethylene oxide or propylene oxide, unsubstituted or halogen- or aromatic-substituted, with an initiator compound containing two or more active hydrogen groups, such as water, ammonia, polyhydric alcohol, or amine. In general, polyether polyols can be prepared by polymerizing alkylene oxides in the presence of an active hydrogen-containing initiator compound. Preferred polyether polyols contain one or more alkylene oxide units in the polyol backbone. Preferred alkylene oxide units are ethylene oxide, propylene oxide, butylene oxide, and mixtures thereof. Preferably, the polyol contains propylene oxide units, ethylene oxide units, or mixtures thereof. In embodiments in which a mixture of alkylene oxide units is included in the polyol, the different units can be arranged randomly or in blocks of each alkylene oxide. In a preferred embodiment, the polyol comprises a propylene oxide chain. In a preferred embodiment, the polyether polyol is a mixture of polyether diols and polyether triols. Preferably, the polyether polyol or mixture has a functionality of at least about 2.0, preferably about 2.0 to 3.0 or more, such as 3.5, 4.0 or more. Preferably, the equivalent weight of the polyether polyol mixture is 80 to 1,200 g / eq.

[0143] More specific examples of polyether polyols include the following: 1. Difunctional polyols (diols), such as poly(alkylene oxide) diols, in which the alkylene groups are C2 to C4, are particularly preferred, particularly poly(propylene oxide) diols, such as poly(ethylene oxide) diol, poly(propylene oxide) diol, poly(butylene oxide) diol and poly(tetramethylene oxide) diol. In a particularly preferred embodiment, the polyether polyol comprises a nominally difunctional poly(propylene oxide) having an equivalent weight of 80 to 2,500, more preferably 200 to 1,100. 2. Trifunctional polyols (triols), such as alkylene oxides initiated with trifunctional polyols, such as trimethylolpropane, where the alkylene groups are C2-C4, are particularly preferred, especially propylene oxide, such as those based on ethylene oxide, propylene oxide, butylene oxide, tetramethylene oxide, and butylene oxide. In a particularly preferred embodiment, the polyether polyol comprises a nominally trifunctional poly(propylene oxide) of equivalent weight between 80 and 2,500 g / eq, more preferably between 80 and 90 g / eq, the polymers being either or not capped with ethylene oxide to modify reactivity. 3. Mixtures of 1 and 2. Mixtures of 1 and 2 are particularly preferred, with a) a nominally difunctional poly(propylene oxide) having an equivalent weight of 100 to 2,500, more preferably 200 to 1,500, and especially preferably 200 to 1,000, and b) a nominally trifunctional poly(propylene oxide) having an equivalent weight of 80 to 90 being particularly preferred.

[0144] In a particularly preferred embodiment, the at least one polyol comprises a mixture of propylene oxide-based diols and triols.

[0145] In addition to at least one polyether polyol, component B may contain an additional polyol. In a preferred embodiment, component B contains a diol or triol having a molecular weight of less than 250 Da. Examples include 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol, with 1,4-butanediol being particularly preferred.

[0146] When used, the diol or triol having a molecular weight of less than 250 Da is preferably present at 2 to 10 wt %, more preferably 4 to 8 wt %, based on the total weight of Component B. In a preferred embodiment, Component B comprises 2 to 10 wt %, more preferably 4 to 8 wt %, butanediol, based on the total weight of Component B.

[0147] In a preferred embodiment, the at least one polyether polyol in Component B comprises a mixture of poly(propylene oxide) diols.

[0148] In another preferred embodiment, the at least one polyether polyol in Component B comprises a poly(propylene oxide) triol.

[0149] In a preferred embodiment, the at least one polyol in Component B comprises a poly(propylene oxide) triol having an average equivalent weight of 1602.8 g / eq.

[0150] Component B preferably contains, based on the total weight of component B, 30 to 45% by weight, more preferably 30 to 40% by weight, particularly preferably 35 to 38% by weight of polyether polyol (b1).

[0151] In a preferred embodiment, Component B comprises, based on the total weight of Component B, 30 to 45% by weight, more preferably 30 to 40% by weight, and particularly preferably 35 to 38% by weight of at least one poly(propylene oxide) triol.

[0152] In another preferred embodiment, component B comprises 30 to 45 wt. %, more preferably 30 to 40 wt. %, and particularly preferably 35 to 38 wt. %, based on the total weight of component B, of poly(propylene oxide) triol having an average equivalent weight of 1602.8 g / eq.

[0153] In a particularly preferred embodiment, component B comprises poly(propylene oxide) triol and butanediol.

[0154] In another particularly preferred embodiment, Component B comprises 30 to 40 wt. % poly(propylene oxide) triol and 4 to 8 wt. % butanediol, based on the total weight of Component B.

[0155] Catalyst (b2) Component B comprises a catalyst capable of catalyzing the reaction of NCO functional groups with OH functional groups.

[0156] Examples of such catalysts include tertiary amine catalysts, organometallic catalysts such as bismuth catalysts, alkyltin carboxylates, oxides, and tin mercaptides.

[0157] Specific examples of tertiary amine catalysts include N-methylmorpholine, N-methylimidazole, triethylenediamine, bis-(2-dimethylaminoethyl)-ether, 1,4-diazabicyclo[2.2.2]octane (DABCO), dimethylcyclohexylamine, dimethylethanolamine, 2,2-dimorpholinyl-diethylether (DMDEE), N,N,N-dimethylaminopropylhexahydrotriazine, dimethyltetrahydropyrimidine, tetramethylethylenediamine, dimethylcyclohexylamine, 2,2-N,N-benzyldimethylamine, Examples of the diamine include dimethylethanolamine, dimethylaminopropylamine, penta-dimethyldiethylenetriamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, N,N',N'-trimethylaminoethylpiperazine, 1,1'-[[3-(dimethylamino)propyl]imino]bispropan-2-ol, 1,3,5-tris[3-(dimethylamino)propyl]hexahydro-1,3,5-triazine, N-N-dimethyldipropylenetriamine, and N,N,N'-trimethylaminoethylethanolamine, with DMDEE being particularly preferred.

[0158] When an organometallic catalyst is used, it is any organometallic catalyst capable of catalyzing the reaction between an isocyanate and a functional group having at least one reactive hydrogen. Examples include bismuth catalysts, metal carboxylates, such as tin carboxylates, zinc carboxylates, etc. Metal alkanoates include stannous octanoate, bismuth octanoate, or bismuth neodecanoate. Preferably, the at least one organometallic catalyst is a bismuth catalyst or an organotin catalyst. Examples include dibutyltin dilaurate, dimethyltin dineodecanoate, dimethyltin mercaptide, dimethyltin carboxylate, dimethyltin dioleate, dimethyltin dithioglycolate, dibutyltin mercaptide, dibutyltin bis(2-ethylhexylthioglycolate), dibutyltin sulfide, dioctyltin dithioglycolate, dioctyltin mercaptide, dioctyltin dioctoate, dioctyltin dineodecanoate, dioctyltin dilaurate. In a particularly preferred embodiment, this is a tin catalyst, particularly preferably dioctyltin mercaptide.

[0159] The catalyst is preferably used in an amount of 0.01 to 0.02% by weight, more preferably 0.015% by weight, based on the total weight of component B.

[0160] In a preferred embodiment, the catalyst is dioctyltin mercaptide, which is used at 0.01 to 0.02% by weight, based on the total weight of component B.

[0161] Optional Ingredients In addition to the thermally conductive filler, Components A and B may additionally contain fillers such as talc, fumed silica, carbon black, zeolites, molecular sieves, and mixtures thereof.

[0162] Manufacturing method The adhesive composition of the present invention is prepared by mixing the ingredients of each component separately, preferably under inert and dry conditions and / or under vacuum, until a homogenous mixture is obtained. After components A and B are mixed, they are stored in separate containers until use.

[0163] How to use In one aspect, the present invention provides a method for bonding two or more substrates, comprising the steps of: (1) providing a thermally conductive two-part polyurethane adhesive, the thermally conductive two-part polyurethane adhesive comprising: (A) (a1) at least one polyisocyanate a first component (isocyanate component) comprising: (B) (b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; and a second component (polyol component) comprising: and wherein component A and / or component B are (i) aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) expandable graphite; (iii) graphene and / or graphite having an aspect ratio greater than 2; (a2, b3) containing a thermally conductive filler; the concentration of the thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 weight percent in the adhesive when Components A and B are mixed together to form the adhesive; (2) mixing component A with component B to produce an adhesive; (3) applying an adhesive to a first substrate; (4) bringing a second substrate into adhesive contact with the first substrate; and (5) Curing the adhesive The present invention provides a method comprising:

[0164] As noted above, a preferred method of providing the component adhesive of the present invention is in an airtight container, such as an airtight sealed tube, etc. The container is opened immediately prior to use.

[0165] The adhesive composition of the present invention may be applied by any application method, such as, for example, spreading, applying through a nozzle, either manually or with robotic equipment.

[0166] In a preferred embodiment, one or both of the first and second substrates are selected from metals, in particular nickel-plated steel and / or aluminum. In another embodiment, one or both of the first and second substrates are selected from metals, including e-coated aluminum, e-coated steel, laser-treated metal surfaces, and metal surfaces treated by plasma or flame. Plasma pretreatment can include plasma treatments, such as Plasma Plus, that further chemically modify or treat the surface. One of these Plasma Plus treatments includes silane functionalization of the metal surface. Further substrates include coated metals and metal surfaces modified with functional foils. The coatings are epoxy-based coatings and acrylic-based coatings. The foils are primarily based on PET.

[0167] Curing begins immediately after components A and B are mixed. Typical curing conditions are 3-7 days at 23°C.

[0168] Effect of the Invention The adhesives of the invention exhibit a thermal conductivity, after curing at 23° C. for 7 days, of at least 1 W / mK, more preferably at least 1.12 W / mK, and especially preferably at least 1.16 W / mK, as measured according to ASTM D5470.

[0169] The adhesives of the present invention exhibit acceptable lap shear strength and retain their lap shear strength even after extended exposure to heat and humidity. The adhesives preferably exhibit a lap shear strength of 4 MPa or greater, more preferably 5 MPA or greater, when tested according to DIN 1465 after 7 days of cure at 23° C. The adhesives of the present invention preferably retain at least 60% of their original lap shear strength after exposure to 100% humidity at 70° C. for 7 days.

[0170] Purpose The properties of the adhesives of the present invention make them particularly suitable for applications requiring good adhesion, good elongation and good thermal conductivity.

[0171] In a preferred embodiment, the adhesives of the present invention are used in the bonding of a cooling unit to a battery assembly, particularly a battery compartment, or directly to a battery pack.

[0172] Particularly preferred embodiments The following are particularly preferred embodiments of the adhesive composition of the present invention. 1. A thermally conductive two-component polyurethane adhesive comprising: (A) (a1) at least one polyisocyanate a first component (isocyanate component) comprising: (B) (b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; and a second component (polyol component) comprising: and wherein component A and / or component B are (i) aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; (iii) graphene and / or graphite having an aspect ratio greater than 2; (a2, b3) containing a thermally conductive filler; the concentration of the thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 weight percent in the adhesive when Components A and B are mixed together to form the adhesive; glue. 2. A thermally conductive two-component polyurethane adhesive produced by mixing a first component (A) and a second component (B), (A)(a1) at least one polyisocyanate, and (B)(b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; Includes; Component A and / or component B (i) aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; (iii) graphene and / or graphite having an aspect ratio greater than 2; (a2, b3) containing a thermally conductive filler; the concentration of the thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 weight percent in the adhesive when Components A and B are mixed together to form the adhesive; glue. 3. A method for bonding two or more substrates, comprising: (1) providing a thermally conductive two-part polyurethane adhesive, the thermally conductive two-part polyurethane adhesive comprising: (A) (a1) at least one polyisocyanate a first component (isocyanate component) comprising: (B) (b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; and a second component (polyol component) comprising: and wherein component A and / or component B are (i) aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; (iii) graphene and / or graphite having an aspect ratio greater than 2; (a2, b3) containing a thermally conductive filler; the concentration of thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 weight percent in the adhesive when Components A and B are mixed together to form the adhesive; (2) mixing component A with component B to produce the adhesive; (3) applying the mixture to a first substrate; (4) bringing a second substrate into adhesive contact with the first substrate; and (5) A step of curing the adhesive The method includes: 4. (1) a first substrate; (2) a second substrate adhesively bonded to the first substrate by a cured adhesive; and A bonded structure comprising: The cured adhesive is obtained by curing a mixture of a first component (A) and a second component (B), the components comprising: (A)(a1) at least one polyisocyanate, and (B) (b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; Includes; Component A and / or component B (i) aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; (iii) graphene and / or graphite having an aspect ratio greater than 2; (a2, b3) containing a thermally conductive filler; the concentration of the thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 weight percent in the adhesive when Components A and B are mixed together to form the adhesive; Bonded construction. 5. Any one of the preceding embodiments, wherein the at least one polyisocyanate has an average NCO functionality greater than 2. 6. Any one of the preceding embodiments, wherein the at least one polyisocyanate has an average NCO functionality greater than 2.1. 7. Any one of the preceding embodiments, wherein the at least one polyisocyanate has an average NCO functionality greater than 2.15. 8. Any one of the preceding embodiments, wherein the at least one polyisocyanate is formed by reaction of at least one molecule having two or more isocyanate groups with a polyol, resulting in a prepolymer terminated with an isocyanate group. 9. Any one of the preceding embodiments, wherein the polyisocyanate is formed by reaction of at least one molecule having two or more isocyanate groups with a polyether polyol, resulting in a prepolymer terminated with an isocyanate group. 10. Any one of the preceding embodiments, wherein the polyisocyanate is formed by the reaction of at least one molecule having two or more isocyanate groups and having an average NCO functionality of greater than 2, more preferably 2.1 or greater, and particularly preferably 2.15 or greater, with a polyether polyol, resulting in a prepolymer terminated with an isocyanate group. 11. Any one of the preceding embodiments, wherein the polyisocyanate is formed by reaction of at least one molecule having two or more isocyanate groups with a poly(propylene oxide)-based polyol, resulting in a prepolymer terminated with an isocyanate group. 12. Any one of the preceding embodiments, wherein the polyisocyanate is formed by reaction of at least one molecule having two or more isocyanate groups with a poly(propylene oxide)-based diol, resulting in a prepolymer terminated with an isocyanate group. 13. Any one of the previous embodiments, wherein the polyisocyanate is a prepolymer formed by reaction of MDI with a polyether polyol. 14. Any one of the previous embodiments, wherein the polyisocyanate is a prepolymer formed by reaction of MDI with a polyol based on poly(propylene oxide). 15. Any one of the previous embodiments, wherein the polyisocyanate is a prepolymer formed by reaction of MDI with a diol based on poly(propylene oxide). 16. Any one of the previous embodiments, wherein the polyisocyanate is a prepolymer formed by reaction of MDI with a first poly(propylene oxide)-based diol having an equivalent weight of 700 g / eq or greater and a second poly(propylene oxide)-based diol having an equivalent weight of 500 g / eq or less. 17. Any one of the previous embodiments, wherein the polyisocyanate is a prepolymer formed by reaction of MDI with a first poly(propylene oxide)-based diol having an equivalent weight of 1001 g / eq and a second poly(propylene oxide)-based diol having an equivalent weight of 215 g / eq. 18. Any one of the preceding embodiments, wherein the polyisocyanate is a prepolymer having an average NCO functionality of greater than 2.0, more preferably 2.1 or greater, and especially preferably 2.15 or greater. 19. Any one of the preceding embodiments, wherein the prepolymer is produced by reacting MDI and / or polymeric MDI with a diol based on poly(propylene oxide), such that the prepolymer has an average NCO content of greater than 2.0, more preferably 2.1 or greater, and especially preferably 2.15 or greater. 20. The polyisocyanate is a prepolymer formed by the reaction of a polyisocyanate with a polyol; Any one of the preceding embodiments, comprising 65-85% by weight polyisocyanate and 15-35% by weight polyol. More preferably, the prepolymer comprises 70-80% by weight polyisocyanate and 20-30% by weight polyol, based on the total weight of the prepolymer. 21. Any one of the preceding embodiments, wherein the polyisocyanate is a prepolymer formed by reaction of 65-85% by weight MDI and 15-35% by weight poly(propylene oxide)-based diol. 22. Any one of the preceding embodiments, wherein the polyisocyanate is a prepolymer having a urethane group ("hard segment") content of greater than 20% by weight, more preferably greater than 29% by weight, and most preferably greater than 35% by weight, based on the total weight of the prepolymer, where the hard segment content is calculated by adding up the weights of aromatic MDI and polymeric MDI used to make the prepolymer and calculating the weight % of the isocyanate component based on the total weight of the prepolymer. 23. Any one of the preceding embodiments, wherein the fully cured adhesive has a hard segment content of greater than 10% by weight, more preferably greater than 20% by weight, and particularly preferably greater than 25% by weight. 24. Any one of the preceding embodiments, wherein the thermally conductive filler is present in Component A or Component B or both, and the concentration of the thermally conductive filler in Component A and / or Component B is sufficient such that when Components A and B are mixed together to form the adhesive, the concentration of thermally conductive filler in the adhesive is 40-80% by weight, more preferably 40-60% by weight, based on the total weight of the adhesive. 25. Any one of the preceding embodiments, wherein the thermally conductive filler is present in Component A at 40 to 80% by weight, preferably 40 to 60% by weight, based on the total weight of Component A. 26. Any one of the preceding embodiments, wherein the thermally conductive filler is present in Component B at 40 to 80 wt%, more preferably 40 to 60 wt%, based on the total weight of Component B. 27. Any one of the preceding embodiments, wherein the thermally conductive filler is present in component A at 40-80 wt%, more preferably 40-60 wt%, based on the total weight of component A, and the thermally conductive filler is present in component B at 40-80 wt%, more preferably 40-60 wt%, based on the total weight of component B. 28. Any one of the preceding embodiments, wherein the thermally conductive filler is present in the final adhesive at a concentration that imparts a thermal conductivity of about 1.1 W / mK or greater after curing at 23° C. for 7 days. 29. Any one of the preceding embodiments, wherein component A and component B are designed to be mixed in a 1:1 volume ratio, and the concentration of the thermally conductive filler in component A is 40-80% by weight, more preferably 50-60% by weight, based on the total weight of component A. 30. Any one of the preceding embodiments, wherein the aluminum trihydroxide has a bimodal particle size distribution. 31. The aluminum trihydroxide has the following particle size distribution: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; Any one of the preceding embodiments, comprising: 32. The aluminum trihydroxide has the following particle size distribution: 1-10% by volume: <1μm, 5-20% by volume: 1-10μm, 6-20% by volume: 10-20μm, 5-40% by volume: 20-50μm, 35-60% by volume: 50-100μm; Any one of the preceding embodiments, comprising: 33. The aluminum trihydroxide has the following particle size distribution: 1-5% by volume: <1μm, 5-15% by volume: 1-10μm, 6-15% by volume: 10-20μm, 20-40% by volume: 20-50μm, 40-70% by volume: 50-100μm; Any one of the preceding embodiments, comprising: 34. The aluminum trihydroxide has the following particle size distribution: ATH1. A first aluminum trihydroxide having the following particle size distribution: D 10 :10μm D 50 : 8μm D 90 :100μm; ATH2. A second aluminum trihydroxide having the following particle size distribution: D 50 : 8μm D 90 :18μm Any one of the preceding embodiments, comprising a mixture of aluminum trihydroxide having: 35. Embodiment 30, wherein the aluminum trihydroxide comprises 75 to 90% by weight, more preferably 80 to 90% by weight, and particularly preferably 85 to 88% by weight, of ATH1, and 10 to 25% by weight, more preferably 10 to 20% by weight, and particularly preferably 12 to 15% by weight, of ATH2, based on the total weight of the aluminum trihydroxide. 36. Any one of the preceding embodiments, wherein the total amount of aluminum trihydroxide in Component A and / or Component B is preferably 40-60 wt.%, more preferably 45-55 wt.%, and particularly preferably 47-52 wt.%, based on the total weight of the respective component. 37. The expandable graphite has the following particle size distribution: 1-10% by volume larger than 50 μm, 20-50% by volume larger than 150 μm, and 30-80% by volume larger than 300 μm; Any one of the preceding embodiments, comprising: 38. The expandable graphite is GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; Any one of the preceding embodiments, wherein the expandable graphite mixture is 39. Embodiment 38, wherein the expandable graphite comprises 40 to 80% by weight, more preferably 45 to 75% by weight, and particularly preferably 50 to 75% by weight, of GR1, and 20 to 60% by weight, more preferably 25 to 55% by weight, and particularly preferably 25 to 50% by weight of GR2, based on the total weight of the expandable graphite. 40. Any one of the preceding embodiments, wherein the total amount of expandable graphite in component A and / or component B is preferably 2-10 wt.%, more preferably 4-8 wt.%, and particularly preferably 6 wt.%, based on the total weight of the respective component. 41. Any one of the preceding embodiments, wherein the graphene has a volume average platelet size of 10-30 μm, more preferably 20-30 μm, and particularly preferably 24-26 μm. 42. Any one of the preceding embodiments, wherein the amount of graphene and / or graphite having an aspect ratio greater than 2 in component A and / or component B is 0.5 to 2 wt. %, more preferably 0.75 to 1.5 wt. %, and particularly preferably 1 to 1.3 wt. %, based on the total weight of the respective component. 43. The thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 44. The thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 45. The thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 46. ​​The thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 47. The thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7 to 12% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 48. The thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9 to 11% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 49. The thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 5-15% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 50. The thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 7-12% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 51. The thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 9-11% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 52. The thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 53. The thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 54. The thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 55. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 56. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 57. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 wt. % of graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 58. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3 to 10 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.5 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 59. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4 to 7 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.75 to 1.5 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 60. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1 to 1.3 wt. % of graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 61. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments. 62. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments. 63. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments. 64. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 65. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 66. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 67. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 68. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7 to 12% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 69. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9 to 11% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 70. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 5-15% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 0.5 to 4 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 71. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 7-12% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 1 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 72. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; 9-11% by weight of expandable graphite, which is an expandable graphite mixture of (iii) 1.5 to 2.5 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 73. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 74. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 75. The thermally conductive filler is (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 76. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 77. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 78. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 wt. % of graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 79. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3 to 10 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.5 to 3 wt. % graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 80. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4 to 7 weight percent of expandable graphite having a particle size distribution in which 1 to 10 volume percent is greater than 50 μm, 20 to 50 volume percent is greater than 150 μm, and 30 to 80 volume percent is greater than 300 μm; (iii) 0.75 to 1.5 weight percent graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 81. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5% by weight of expandable graphite having a particle size distribution in which 1 to 10% by volume is larger than 50 μm, 20 to 50% by volume is larger than 150 μm, and 30 to 80% by volume is larger than 300 μm; (iii) 1 to 1.3 wt. % of graphene and / or graphite having an aspect ratio greater than 2; Any one of the preceding embodiments. 82. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments. 83. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments. 84. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) a particle size distribution of: 1-20% by volume: <1 μm, 10-30% by volume: 1-10 μm, 5-30% by volume: 10-20 μm, >10% by volume: 20-50 μm, >20% by volume: 50-100 μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 wt. % of graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments. 85. The thermally conductive filler is (i) ATH1. A first aluminum trihydroxide having the following particle size distribution: D 10 :10μm D 50 : 8μm D 90 :100μm; ATH2. A second aluminum trihydroxide having the following particle size distribution: D 50 : 8μm D 90 :18μm; a mixture of aluminum trihydroxide having a particle size distribution of; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; Expandable graphite, which is an expandable graphite mixture of (iii) graphene having a volume average platelet size of 10 to 30 μm, more preferably 20 to 30 μm, particularly preferably 24 to 26 μm; Any one of the preceding embodiments. 86. Any one of the preceding embodiments, wherein the at least one polyether polyol (b1) comprises a mixture of propylene oxide-based diols and triols. 87. Any one of the preceding embodiments, wherein the at least one polyether polyol in component B comprises a poly(propylene oxide) triol. 88. Any one of the preceding embodiments, wherein the at least one polyol in component B comprises a poly(propylene oxide) triol having an average equivalent weight of 1602.8 g / eq. 89. Any one of the preceding embodiments, wherein component B comprises 30 to 45 wt. %, more preferably 30 to 40 wt. %, and particularly preferably 35 to 38 wt. % of the polyether polyol (b1), based on the total weight of component B. 90. Any one of the preceding embodiments, wherein component B comprises 30 to 45 wt.%, more preferably 30 to 40 wt.%, and particularly preferably 35 to 38 wt.%, of at least one poly(propylene oxide) triol, based on the total weight of component B. 91. Any one of the preceding embodiments, wherein component B comprises 30 to 45 wt.%, more preferably 30 to 40 wt.%, and especially preferably 35 to 38 wt.%, based on the total weight of component B, of a poly(propylene oxide) triol having an average equivalent weight of 1602.8 g / eq. 92. Any one of the preceding embodiments, wherein component B comprises poly(propylene oxide) triol and butanediol. 93. Any one of the preceding embodiments, wherein component B comprises 30 to 40 wt. % poly(propylene oxide) triol and 4 to 8 wt. % butanediol, based on the total weight of component B. 94. Any one of the preceding embodiments, wherein the catalyst is selected from a tertiary amine catalyst, an organometallic catalyst, such as a bismuth catalyst, an alkyltin carboxylate, oxide, and a tin mercaptide. 95. Any one of the preceding embodiments, wherein the catalyst is dioctyltin mercaptide. 96. Any one of the preceding embodiments, wherein the catalyst is used at 0.01 to 0.0.02 wt %, more preferably 0.015 wt %, based on the total weight of Component B. 97. The thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 98. The thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 99. The thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 100. The thermally conductive filler is (i) 75 to 95% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5 to 15% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.5-4% by weight of graphite in the form of particles having Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 101. The thermally conductive filler is (i) 80 to 90% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 7-12% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1-3% by weight of graphite in the form of particles having Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 102. The thermally conductive filler is (i) 85 to 88% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 9-11% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1.5-2.5% by weight of graphite in the form of particles having Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 103. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments. 104. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments. 105. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments. 106. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 40 to 60% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 3-10% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.5-3% by weight of graphite in the form of particles having Any one of the preceding embodiments. 107. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 45 to 55% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 4-7% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.75-1.5% by weight of graphite in the form of particles having Any one of the preceding embodiments. 108. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) 48 to 50% by weight of aluminum trihydroxide having a polymodal (preferably bimodal) particle size distribution; (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1-1.3% by weight of graphite in the form of particles having Any one of the preceding embodiments. 109. The thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15% by weight of expandable graphite; (iii) 0.5 to 4 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 110. The thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7-12% by weight of expandable graphite; (iii) 1 to 3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 111. The thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9-11% by weight of expandable graphite; (iii) 1.5 to 2.5 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 112. The thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 75 to 95% by weight of aluminum trihydroxide having the formula: (ii) 5 to 15% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.5-4% by weight of graphite in the form of particles having Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 113. The thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 80 to 90% by weight of aluminum trihydroxide having the formula: (ii) 7-12% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1-3% by weight of graphite in the form of particles having Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 114. The thermally conductive filler is (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 85 to 88% by weight of aluminum trihydroxide having the formula: (ii) 9-11% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1.5-2.5% by weight of graphite in the form of particles having Any one of the preceding embodiments, wherein the weight percentage is based on the total weight of the thermally conductive filler. 115. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3-10% by weight of expandable graphite; (iii) 0.5 to 3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments. 116. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4-7% by weight of expandable graphite; (iii) 0.75 to 1.5 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments. 117. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) 1 to 1.3 weight percent graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments. 118. The thermally conductive filler is (i) ATH1. A first aluminum trihydroxide having the following particle size distribution: D 10 :10μm D 50 : 8μm D 90 :100μm; ATH2. A second aluminum trihydroxide having the following particle size distribution: D 50 : 8μm D 90 :18μm; a mixture of aluminum trihydroxide having a particle size distribution of; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; Expandable graphite, which is an expandable graphite mixture of (iii) graphite having an aspect ratio greater than 3, more preferably greater than 4; Any one of the preceding embodiments. 119. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 40 to 60% by weight of aluminum trihydroxide having the formula: (ii) 3-10% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.5-3% by weight of graphite in the form of particles having Any one of the preceding embodiments. 120. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 45 to 55% by weight of aluminum trihydroxide having the formula: (ii) 4-7% by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 0.75-1.5% by weight of graphite in the form of particles having Any one of the preceding embodiments. 121. The adhesive obtained by mixing component A and component B has, based on the total weight of the adhesive, (i) A particle size distribution of: 1-20% by volume: <1μm, 10-30% by volume: 1-10μm, 5-30% by volume: 10-20μm, >10% by volume: 20-50μm, >20% by volume: 50-100μm; 48 to 50% by weight of aluminum trihydroxide having the formula: (ii) 5.5 to 6.5 percent by weight of expandable graphite; (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 1-1.3% by weight of graphite in the form of particles having Any one of the preceding embodiments. 122. The thermally conductive filler is (i) ATH1. A first aluminum trihydroxide having the following particle size distribution: D 10 :10μm D 50 : 8μm D 90 :100μm; ATH2. A second aluminum trihydroxide having the following particle size distribution: D 50 : 8μm D 90 :18μm; a mixture of aluminum trihydroxide having a particle size distribution of; (ii) GR1. A first expandable graphite, 75% by volume of which has a particle size of <150 μm; GR2. A second expandable graphite, 80% by volume of which has a particle size of >300 μm; Expandable graphite, which is an expandable graphite mixture of (iii) having an aspect ratio of more than 2 and a D of 80 to 110 μm, more preferably 85 to 95 μm 90 Graphite in the form of particles having; Any one of the preceding embodiments. EXAMPLES

[0173] [Table 1]

[0174] [Table 2]

[0175] [Table 3]

[0176] Adhesive Formulation Component A (isocyanate) and component B (polyol) were prepared in a laboratory scale mixer, a 4-5 L planetary mixer. The raw materials listed in Table 2 were used.

[0177] To prepare Component B (polyol), the ingredients listed in Table 2 were blended in a planetary mixer until uniform.

[0178] To prepare Component A (isocyanate), an isocyanate-terminated prepolymer was prepared by first mixing the polyol raw materials (diols and / or triols) of Component A. The isocyanate raw materials were then added with stirring at ambient temperature. The filler raw materials were then added and the mixture was heated to 40° C. and stirred for 45 minutes until the mixture was clear. The mixture was then heated to 70° C. over 30 minutes. A vacuum of 80 mbar was applied and mixing was continued for an additional 60 minutes. Heating was discontinued and the mixture was stirred under vacuum until a temperature of 40° C. was reached. The vacuum was released under nitrogen and Component A was stored in a foil package under nitrogen until use.

[0179] Components A and B were stored separately until use. The components were then mixed in a 1:1 volume ratio. The resulting adhesive was cured at 23°C for 7 days and the properties were measured.

[0180] Test Method Thermal Conductivity Thermal conductivity was measured according to ASTM 5470. A thermal interface material tester from ZFW Stuttgart was used for testing. Measurements were performed in Spaltplus mode at thicknesses between 1.8 and 1.2 mm. Absolute thermal conductivity λ (W / mK) is reported.

[0181] Elongation at break The elongation at break was determined according to DIN 527-1.

[0182] Lap shear strength Lap shear strength was measured according to DIN 1465. Samples were e-coated substrates with dimensions 25mm x 12.5mm x 0.5mm, adhesive area 25mm x 20mm, and adhesive thickness 0.5mm. The adhesive was cured for 7 days at 23°C. Lap shear strength was also evaluated after exposure at 70°C and 100% relative humidity (RH) for 7 days.

[0183] [Table 4]

[0184] [Table 5]

[0185] result Inventive Example 1 achieves excellent thermal conductivity of 1.2 W / mK, excellent lap shear strength, and excellent retention of lap shear strength after exposure to heat and moisture. Of the comparative examples, only Comparative Example 3 exhibits acceptable thermal conductivity, but suffers from impaired lap shear strength and has unacceptable retention of lap shear strength after exposure to heat and moisture.

Claims

1. A thermally conductive two-component polyurethane adhesive comprising: (A) (a1) at least one polyisocyanate a first component (isocyanate component) comprising: (B) (b1) at least one polyether polyol, and (b2) at least one catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups; a second component (polyol component) comprising: and component A and / or component B comprises (i) aluminum trihydroxide having a multimodal particle size distribution; (ii) expandable graphite; (iii) graphene, and / or graphite having an aspect ratio greater than 2; (a2, b3) a thermally conductive filler comprising: the concentration of the thermally conductive filler in Component A and / or Component B is sufficient to result in a thermally conductive filler concentration of 40 to 80 wt. % in the adhesive when Components A and B are mixed together to form the adhesive; glue.

2. The adhesive of claim 1 , wherein the at least one polyisocyanate has an average NCO functionality greater than 2.

3. The adhesive of claim 1 , wherein the at least one polyisocyanate has an average NCO functionality greater than 2.

1.

4. The adhesive of claim 1 , wherein said at least one polyisocyanate has an average NCO functionality greater than 2.

15.

5. 10. The adhesive of claim 1, wherein the at least one polyisocyanate is formed by the reaction of at least one molecule having two or more isocyanate groups with a polyol, resulting in a prepolymer terminated with isocyanate groups.

6. 10. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer formed by the reaction of at least one molecule having two or more isocyanate groups with a polyether polyol, resulting in a prepolymer terminated with isocyanate groups.

7. 2. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer formed by reacting at least one molecule having two or more isocyanate groups and an average NCO functionality of more than 2, more preferably 2.1 or more, and particularly preferably 2.15 or more, with a polyether polyol, resulting in a prepolymer terminated with isocyanate groups.

8. 10. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer formed by the reaction of at least one molecule having two or more isocyanate groups with a poly(propylene oxide)-based polyol, resulting in a prepolymer terminated with isocyanate groups.

9. 10. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer formed by the reaction of at least one molecule having two or more isocyanate groups with a poly(propylene oxide)-based diol, resulting in a prepolymer terminated with isocyanate groups.

10. 10. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer formed by the reaction of MDI with a polyether polyol.

11. 10. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer formed by the reaction of MDI with a polyol based on poly(propylene oxide).

12. 10. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer formed by the reaction of MDI with a poly(propylene oxide)-based diol.

13. 10. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer formed by the reaction of MDI with a first poly(propylene oxide)-based diol having an equivalent weight of 700 g / eq or greater and a second poly(propylene oxide)-based diol having an equivalent weight of 500 g / eq or less.

14. 10. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer formed by the reaction of MDI with a first poly(propylene oxide)-based diol having an equivalent weight of 1001 g / eq and a second poly(propylene oxide)-based diol having an equivalent weight of 215 g / eq.

15. 10. The adhesive of claim 1, wherein the polyisocyanate is a prepolymer having an average NCO functionality greater than 2.0, more preferably 2.1 or greater.